MERETAS PERAN GANDA ISTRI NELAYAN DALAM HOUSEHOLD ECONOMY EMPOWERMENT - Bayu Tri Cahya; Muhammad Soni Salahuddin; Jadzil Baihaqi (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2019)
Abstract. Demak Regency has a coastal area which is one of the livelihoods of fishermen, namely Kampung Rajungan Demak. A part of social potential in Coastal society is women especially fishermen wives. Coastal women has an important role at fishing households. Wives should only be responsible for the domestic sector, but this developes when women fisherman play a role to looking for a living. The involvement of the women fisherman in earning a living creates a double rol in the household. This research assesses the dual role of woman fisheman in the household economy. This research was conducted in Betahwalang Village, Bonang District, Demak Regency. The purpose of this study is to reveal the dual role of women fisherman in empowering the household economy. This research used qualitaive data analysis method with interview, observation and documentation data collection techniques. The results of this research showed that the double role of women fisherman provides a significant contribution in improving the household economy.Abstrak. Kabupaten Demak memiliki wilayah pesisir yang menjadi salah satu sumber mata pencaharian para nelayan yakni Kampung Rajungan Demak. Salah satu komponen potensi sosial dalam masyarakat pesisir adalah kaum perempuan khususnya istri nelayan. Perempuan pesisir memiliki peran penting dalam rumah tangga nelayan. Seyogyanya istri hanya bertanggung jawab pada sektor domestik, namun hal tersebut berkembang apabila kaum istri ikut berperan dalam mencari nafkah. Keterlibatan istri dalam mencari nafkah menimbulkan peran ganda di dalam rumah tangga. Penelitian ini menggambarkan peran ganda istri nelayan dalam ekonomi rumah tangga. Penelitian ini dilakukan di Desa Betahwalang Kecamatan Bonang Kabupaten Demak. Tujuan kajian artikel ini adalah mengungkap peran ganda istri nelayan dalam penguatan ekonomi rumah tangga. Metode analisa data yang digunakan adalah metode kualitatif dengan teknik pengumpulan data wawancara, observasi dan dokumentasi. Dari hasil penelitian tersebut menggambarkan bahwa peran ganda istri nelayan memberikan kontribusi yang signifikan dalam penguatan ekonomi rumah tangga.